Relation between physiological and some agronomic characteristics in selected genotypes of wheat in drought stress condition - Naroui Rad, M. R; Jaafar, Hawa Z. E; Moghaddam, Hossein Akbari; Poodineh, Omid; Moayedi, Hossein (WFL Publisher, 2010)
In order to evaluate selected genotypes of wheat in drought stress condition, 30 genotypes of bread wheat differing in drought resistance were selected from segregation generations and grown only under drought stress conditions in Zahak Agriculture Research Station. Each genotype was sown in 6 lines with 3 m length and 30 cm space apart. To evaluate their characteristics, 3 plants per plot from middle of the plot were sampled. Results of factor analysis showed there were six factors that determined 74% of variation among characteristics, and regression by stepwise method determined the canopy temperature has seemed to have an effective role in seed yield. Correlation analysis showed that canopy temperature had positive and significant relation with grain yield.